Book Reviews - Mintz, Joel A.; Atlas, Seth J. (Columbia Journal of Environmental Law, 2020)
AIR POLLUTION: FEDERAL LAW AND ANALYSIS. By David P. Currie. Wilmette, Illinois: Callahan and Company, 1981. Pp. xii, 602. $75.00. CONTROLLING TECHNOLOGY: GENETIC ENGINEERING AND THE LAW. By Yvonne M. Cripps. New York: Praeger Publishers. 1980. Pp. xii, 154.